Diagnostic overview of the illegal trade in primates and law enforcement in Peru. Issue 11 (18th December 2015) - Shanee, Noga; Mendoza, A. Patricia; Shanee, Sam
Abstract : Peru has one of the richest primate faunas of any country. The illegal trade in wild primates is one of the largest threats to this fauna in Peru. We characterize the illegal trade in primates through empirical and ethnographic data. We collected data from traffic routes and centers throughout Peru and evaluate current efforts to combat this traffic. Based on our findings from 2, 070 instances of wildlife crime involving 6, 872 primates, we estimate the domestic trade in primates for pets and bushmeat in Peru in the hundreds of thousands per year, with the larger bodied Atelidae facing the highest direct consequences. We found that government authorities lack sufficient staff, capacity, resources, infrastructure, and protocols to efficiently combat illegal trade in primates. Also, the complicated legal framework and lack of cooperation and antagonism with the public further limit these efforts. Wildlife authorities in Peru are able to confiscate only a fraction of primates traded and mostly intervene in cases of private pet owners rather than traffickers. We estimate that the current rate of illegal trade in primates is comparable to levels of trade prior to the 1973 ban on primates' exportation. The combination of direct observations on primate trade and ethnographic data allows a comprehensive look at primate trade in Peru. We call upon decision makers and international funders to channel their efforts toward "on the ground" actions such as increasing the ability of the authorities to act, giving them "in action" training in law enforcement and establishing strict control measures against corruption. Am. J. Primatol. 79:e22516, 2017. © 2015 Wiley Periodicals, Inc.